Comparative evaluation of border molding using two different techniques in maxillary edentulous arches: A clinical study - Anchal Qanungo; Meena Ajay Aras; Vidya Chitre; Ivy Coutinho; Praveen Rajagopal; Ashwin Mysore (Wolters Kluwer Medknow Publications, 2016)
Purpose: The aim of this in vivo study was to compare the single-step border molding technique using injectable heavy viscosity addition silicone with sectional border molding technique using low fusing impression compound by evaluating the retention of heat cure trial denture bases. Materials and Methods: Ten completely edentulous patients in need of prostheses were included in this study. Two border molding techniques, single-step (Group 1) and sectional (Group 2), were compared for retention. Both border molding techniques were performed in each patient. In both techniques, definitive wash impression was made with light viscosity addition silicone. The final results were analyzed using paired t-test to determine whether significant differences existed between the groups. Results: The t-value (3.031) infers that there was a significant difference between Group 1 and Group 2 (P = 0.014). The retention obtained in Group 2 (mean = 9.05 kgf) was significantly higher than that of Group 1 (mean = 8.26 kgf). Conclusion: Sectional border molding technique proved to be more retentive as compared to single-step border molding although clinically the retention appeared comparable.